Family portrait: The father figure in the work of Helena Almeida - Coelho, Maria Luísa (2020)
Helena Almeida (1934-2018) is one of the most interesting and relevant artists in Portuguese contemporary art, having produced an oeuvre of great integrity and consistency, in which the body of the artist and processes of self-representation (always in an ambivalent, subversive and transgressive relation with that same art tradition) took centre stage. Taking the work Family portrait (1979) as its starting point, this article will explore the relation Almeida had with the familiar, be it in personal, artistic or national terms, as all these dimensions of the concept cannot be dissociated from each other when we look at this artist’s oeuvre.